PERAN PONDOK PESANTREN TAHFIDZUL QUR’AN AL-IKHLASH MOJOLABAN DALAM PEMBERDAYAAN MASYARAKAT SEKITAR - Henny Sri Kusumawati; Amalia Sholekhah; Afifah Qonita (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This writing aims to The empowerment program for the community is very important in order to show that Islamic boarding schools, especially salaf Islamic boarding schools, are not only able to play a role in the religious field but also able to play a role in empowering the surrounding community both in the fields of education, social, and Islamic preaching. In addition to being a place for Islamic religious education, Islamic boarding schools also participate in building the younger generation. So that the existence of Islamic boarding schools can provide real benefits to the surrounding environment. In general, the role of Islamic boarding schools in society consists of five aspects. Namely the role for Islamic religious civilization, education, social, economic and cultural The role of Islamic boarding schools in the form of community empowerment in substance clearly leads to a means of establishing communication between Islamic boarding schools and the surrounding community.